2021
DOI: 10.1136/bjophthalmol-2021-319450
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy identifies corneal nerve fibre loss and increased dendritic cells in patients with long COVID

Abstract: Background/AimsLong COVID is characterised by a range of potentially debilitating symptoms which develop in at least 10% of people who have recovered from acute SARS-CoV-2 infection. This study has quantified corneal sub-basal nerve plexus morphology and dendritic cell (DC) density in patients with and without long COVID.MethodsForty subjects who had recovered from COVID-19 and 30 control participants were included in this cross-sectional comparative study undertaken at a university hospital. All patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 33 publications
(24 reference statements)
3
70
0
1
Order By: Relevance
“…The hypothesis that some long COVID symptoms reflect underlying small-fiber pathology is supported by research observation of small-fiber loss applying in vivo corneal confocal microscopy to patients with long COVID. 9 As with other post-COVID neurologic illnesses, susceptibility to inflammatory mediators appears essential. Autopsy study of post-COVID patients identified neuritis with perivascular macrophage infiltrates but no viral antigens, implicating inflammatory immune responses rather than direct infection.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that some long COVID symptoms reflect underlying small-fiber pathology is supported by research observation of small-fiber loss applying in vivo corneal confocal microscopy to patients with long COVID. 9 As with other post-COVID neurologic illnesses, susceptibility to inflammatory mediators appears essential. Autopsy study of post-COVID patients identified neuritis with perivascular macrophage infiltrates but no viral antigens, implicating inflammatory immune responses rather than direct infection.…”
Section: Discussionmentioning
confidence: 99%
“…We have pioneered the rapid noninvasive technique of corneal confocal microscopy (CCM) to demonstrate corneal nerve fiber loss in a number of central 14 18 and peripheral 19 22 neurodegenerative diseases and increased Langerhans cells (LCs) in inflammatory and immune-mediated neuropathies 23 27 and long-coronavirus disease (COVID). 28 Moreover, we have shown that CCM has equivalent diagnostic utility to quantitative sensory testing and enhances the diagnosis of small fiber neuropathy. 29 …”
Section: Introductionmentioning
confidence: 88%
“…There are small studies which indicate both large ( 68 ) and small ( 69 ) fiber neuropathy in patients following COVID-19, although this may reflect nerve damage associated with severe disease and critical illness ( 70 , 71 ). However, we have recently shown corneal nerve loss and increased dendritic cells in a cohort of patients 12 weeks after relatively mild COVID-19, particularly those with neuropathic and fibromyalgia like symptoms who fulfilled the criteria for long-COVID ( Figure 3 ) ( 72 ).…”
Section: Ccm In Peripheral Neuropathiesmentioning
confidence: 99%